Causes of accidental childhood deaths in China in 2010: A systematic review and analysis - Kit Yee Chan; Xin-wei Yu; Jia-peng Lu; Alessandro Rhyll Demaio; Kirsty Bowman; Evropi Theodoratou (Edinburgh University Global Health Society, 2015)
Background Infectious causes of childhood deaths in the world have decreased substantially in the 21st century. This trend has exposed accidental deaths as an increasingly important future challenge. Presently, little is known about the cause structure of accidental childhood deaths in low- and middle-income country (LMIC) settings In this paper, we aim to establish cause structure for accidental deaths in children aged 0-4 years in China in the year 2010. Methods In this paper, we explored the database of 208 multi-cause child mortality studies in Chinese that formed a basis for the first published estimate of the causes of child deaths in China (for the year 2008). Only five of those studies identified specific causes of accidental deaths. Because of this, we searched the Chinese medical literature databases CNKI and WanFang for single-cause mortality studies that were focused on accidental deaths. We identified 71 further studies that provided specific causes for accidental deaths. We used epidemiological modeling to estimate the number of accidental child deaths in China in 2010 and to assign those deaths to specific causes. Results In 2010, we estimated 314 581 deaths in children 0-4 years in China, of which 31 633 (10.1%) were accidental. Accidental deaths contributed 7240 (4.0%) of all deaths in neonatal period, 8838 (10.5%) among all post-neonatal infant deaths, and 15 554 (31.7%) among children with 1-4 years of age. Among four tested models, the most predictive was used to establish the likely cause structure of accidental deaths in China. We estimated that asphyxia caused 9490 (95% confidence interval (CI) 8224-11 072), drowning 5694 (95% CI 5061-6327), traffic accidents 3796 (95% CI3163-4745), poisoning 3163 (95% CI 2531-3796) and falls 2531 (95% CI 2214-3163) deaths. Based on medians from a few rare studies, we also predict 633 (95% CI 316-1265) deaths to be due to burns and 316 (95% CI 0-633) due to falling objects. Together, these 7 causes explain more than 80% of all accidental deaths when modeling is primarily used, and more than 95% when the analysis is based purely on medians from the 76 available studies. Conclusions Reduction in global child mortality is a leading political priority and accidental deaths will soon emerge as one of the main challenges. In this paper we provided a detailed breakdown of causes of these deaths in a large middle-income country. We noted that, wherever the share of accidental deaths among all child deaths is increased, drowning is more likely to be the leading cause; asphyxia seems to be equally important in all contexts, while traffic accidents, poisoning and falls are relatively more important in contexts where the overall share of accidents to all child deaths is low.